Gomphonella olivacea (Bacillariophyceae) - a new phylogenetic position for a well-known taxon, its typification, new species and combinations - Jahn, Regine; Kusber, Wolf-Henning; Skibbe, Oliver; Zimmermann, Jonas; Van, Anh Tu; Buczkó, Krisztina; Abarca, Nélida (Plant ecology and evolution, 2019)
Background and aims - Within the project "German Barcode of Life - Diatoms" common diatoms of German waters were routinely isolated and cultivated. In order to understand the taxonomy and phylogeny of the genus Gomphonema , one of the most common taxa of Central Europe, known currently either under the name Gomphonema olivaceum in Europe or Gomphoneis olivacea in America, was studied. Methods - Twenty unialgal strains were established from five different water bodies in Germany and one from Lake Balaton, Hungary, which supplied molecular data (18S V4 and rbc L) besides morphometric and ultrastructural data. In addition, on eight populations from different water bodies including the type from Denmark, morphometric and micromorphological studies by light and scanning electron microscopy were performed. Key results - Molecular and micromorphological data show that the target taxon neither belongs to Gomphonema Ehrenb. nor to Gomphoneis Cleve. By reinstating the genus name Gomphonella Rabenh., the nomenclatural and taxonomic enigma of this taxon is solved, and with the presentation of the type by Hornemann the authorship of the epithet is clarified. Molecular data for the unialgal strains and several environmental clones show that there is more diversity in the Gomphonella olivacea clade than can be identified morphologically. In addition, the establishment of the new species Gomphonella coxiae and Gomphonella acsiae is supported. The molecular data classified Gomphonella species as belonging to the Cymbellales but not to the Gomphonemataceae. In addition, molecular data put Gomphoneis tegelensis R.Jahn & N.Abarca also into Gomphonella. In order to make the genera Gomphoneis and Gomphonema monophyletic, their astigmate members are transferred to Gomphonella. Conclusions - The results clarify that the gomphonemoid outline is not restricted to the family Gomphonemataceae but seem to be distributed across the entire order Cymbellales. This is shown in this paper for the revived genus Gomphonella, which contains the astigmate group of Gomphoneis and Gomphonema besides the longly disputed G. olivacea. Only a polyphasic approach, combining molecular and micromorphological data for taxonomy, nomenclatural evaluation, and observations from clonal cultures can reveal the full intricacies of evolutionary relations.